Pultruded Natural Fibre Reinforced Composites: Preparation, Properties And Applications - Md Akil, Hazizan; Zamri, Hafiz; Shahidan, Helfy Affzan; Zainal Arifin, Mohd Ishak; Abu Bakar, Azhar (2011)
Environmentally friendly composites are today highly required by utilizing natural fibers as reinforcement combined with biodegradable polymer as matrices.